STRUKTUR ILMU DAKWAH DALAM DISKURSUS Suatu Tinjauan Filsafat Ilmu - Ichwansyah Tampubolon (IAIN Padangsidimpuan, 2017)
There is no concensus among scholars about structure of Discipline of Da`wah.Ontologically, the Discipline of Da`wah not only focuses on study of devinedoctrines of da`wah as the material objects which are embedded in Alquran andhadith, but also study of the activities of da`wah as the formal objects.Epistemologically, it takes not only methodologies of social sciences in it’sresearch, but also uses methodologies of humanities sciences and that of religiousones. Axiologically, the orientations of Discipline of Da`wa is not only to preachIslamic mission, practically, but also to explain or to describe the realities ofDa`wa, theoritically. Structuring Discipline of Da`wah is still on going process oron going formation.